Use of propolis in the oral cavity in cancer patients: A literature review (Research, Society and Development, 2024)
The presence of oral alterations in cancer patients is frequent, due to the aggressiveness of chemotherapy or radiotherapy treatment, causing discomfort, pain, and worsening of quality of life. Adjuvant therapies that help prevent or minimize these alterations are frequently used, such as herbal medicines. Propolis is an herbal compound of choice for the auxiliary treatment of side effects of cancer therapies, due to its antimicrobial, anti-inflammatory, antioxidant, and anticancer properties. The objective of this literature review was to address the use of propolis in cancer patients as a way of preventing or treating the adverse effects caused by chemotherapy and radiotherapy. For this purpose, articles from the PUBMED, LILACS, and SCIELO databases, published between 2014 and 2024, in Portuguese, Spanish, and English, were selected. Review studies, experimental research, and case reports were selected, excluding opinion articles and monographs. The mechanism of action of propolis as an adjuvant in cancer treatment has demonstrated the potential to induce cell apoptosis, enhancing the beneficial effects of chemotherapy and radiotherapy. However, its use should be cautious, since prolonged use or in high doses can cause adverse reactions of hypersensitivity and toxicity. Its use is contraindicated for patients with a history of allergy to bee products, and those using anticoagulants. In short, propolis emerges as a promising resource in oncology, with the capacity to contribute significantly to the well-being and quality of life of patients during cancer treatment.